2003
DOI: 10.1177/000348940311200211
|View full text |Cite
|
Sign up to set email alerts
|

Cytolysis of Eosinophils in Nasal Secretions

Abstract: It is still unknown how eosinophils degranulate in nasal mucus. Currently, cytolysis is being reevaluated as the mode of degranulation of eosinophils in allergic nasal mucosa. To examine whether eosinophils migrating to the nasal mucus degranulate by cytolysis, we sampled nasal mucus from 9 patients with nasal allergy and observed it under electron and light microscopes. Both intact and necrotic eosinophils were observed in the nasal mucus. Although the total eosinophil count in the nasal mucus was not correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…EM studies that can recognize the distinct core-containing ultrastructure of membrane bound, extracellular eosinophil granules have suggested that cytolysis is a common mechanism of for the release and deposition of membrane-bound granules extracellularly in tissue biopsies of patients with atopic dermatitis [18], nasal allergy [19,20], nasal polyps [21] and in other upper airway respiratory mucosal disorders [22]. The functioning of cell-free granules and their capacities to mobilize their contents of preformed proteins had not been never been investigated.…”
Section: Free Extracellular Eosinophil Granules and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…EM studies that can recognize the distinct core-containing ultrastructure of membrane bound, extracellular eosinophil granules have suggested that cytolysis is a common mechanism of for the release and deposition of membrane-bound granules extracellularly in tissue biopsies of patients with atopic dermatitis [18], nasal allergy [19,20], nasal polyps [21] and in other upper airway respiratory mucosal disorders [22]. The functioning of cell-free granules and their capacities to mobilize their contents of preformed proteins had not been never been investigated.…”
Section: Free Extracellular Eosinophil Granules and Diseasementioning
confidence: 99%
“…Clusters of intact extracellular eosinophil granules were found in asthmatic sputum samples [23] and in association with sinus tissue of patients with chronic rhinosinusitis [25,32]. Analysis of the nasal mucus of patients with nasal allergy [20] and skin of patients with chronic idiophatic urticaria [27] revealed the existence of cytolytic eosinophils and extracellular deposition of eosinophil granules. EM analyses of skin biopsies of patients presenting with atopic dermatitis showed the presence of membrane-bound eosinophil granules outside the cell between collagen bundles and in dermis without recognizable adjacent eosinophils [18].…”
Section: Free Extracellular Eosinophil Granules and Diseasementioning
confidence: 99%
“…Eosinophil cytolysis seems to occur in most cases of an active allergic inflammation [126]. This widespread occurrence is reflected by the observations of cytolytic eosinophils, or clusters of membrane-free eosinophil granules, in patients with asthma [127][128][129], allergic rhinitis [130], atopic dermatitis [123], nasal polyposis, as well as various parasitic infections [131].…”
Section: Eosinophil Cytolysismentioning
confidence: 99%
“…A third, as yet, enigmatic mode of eosinophil degranulation arises from cytolysis of eosinophils that deposits intact membrane-bound eosinophil granules extracellularly (7). With their unique ultrastructure, free extracellular eosinophil granules have been recognized in the airways or tissues in association with diverse disorders, including allergic asthma and rhinitis, dermatitis, helminth infections, eosinophilic esophagitis, and urticaria (7)(8)(9)(10)(11)(12). Neither functional roles nor consequences of cell-free extracellular eosinophil granules have been delineated.…”
mentioning
confidence: 99%